1996
DOI: 10.1088/0953-4075/29/8/017
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron impact excitation of the nitrogen molecule: optically forbidden transitions

Abstract: Ab initio calculations are performed on the e − -N 2 scattering system, at low impact energies, using the R-matrix technique. The X 1 + g ground state and the lowest seven valence excited states, A 3 + u , B 3 g , W 3 u , B 3 − u , a 1 − u , a 1 g and w 1 u , of N 2 are included in the close coupling expansion with each state being represented by a configuration interaction wavefunction in a hybrid orbital set. Various approximations for the representation of the correlation between the target and the incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 43 publications
14
64
3
Order By: Relevance
“…One reaction mechanism postulated by Zipf and Prasad (), based on their laboratory work, is that secondary electron impact from energetic electron precipitation (EEP) promotes N 2 to the excited triplet state. N2()X1normalΣnormalg++eN2()A3normalΣnormalu++e, where the N 2 (A 3 Σ u + ) state lies 7.63 eV above the N 2 (X 1 Σ g + ) ground state (Gillan et al, ). In a similar manner, reaction can be induced by photoelectrons (energetic electrons produced by photo‐ionization of atmospheric species; Nagy & Banks, ).…”
Section: Introductionmentioning
confidence: 99%
“…One reaction mechanism postulated by Zipf and Prasad (), based on their laboratory work, is that secondary electron impact from energetic electron precipitation (EEP) promotes N 2 to the excited triplet state. N2()X1normalΣnormalg++eN2()A3normalΣnormalu++e, where the N 2 (A 3 Σ u + ) state lies 7.63 eV above the N 2 (X 1 Σ g + ) ground state (Gillan et al, ). In a similar manner, reaction can be induced by photoelectrons (energetic electrons produced by photo‐ionization of atmospheric species; Nagy & Banks, ).…”
Section: Introductionmentioning
confidence: 99%
“…) + e -(6.17 eV) 3.6x10 -10 [22] 4b N 2 + e - N 2 (B 3  g ) + e -(7.35 eV) 3.1x10 -10 [22] 5 N 2 + e - N 2 (a 1  g ) + e - ( 17 C 2 H 5 OH + e - C 2 H 5 + OH + e -(7.5 eV) 1.0x10 -9 [28] 18 C 2 H 5 OH + e - CH 3 CHOH + H + e -(7.5 eV) 1.0x10 -9 [28] 19 C 2 H 5 OH + e - C 2 H 5 OH + + 2e -(10.48 eV) 1.0x10 -12 [28] The nonisothermality of discharge plasma is characterized by two character temperatures: 1) average electronic temperature T e that is determined by the EEDF, i.e., by the applied electric field E/N, and 2) gas kinetic temperature T that is determined by conditions of convective cooling in the gas channel with liquid wall, i.e., by temperature of surrounding liquid (T  350K). In fact, the ratio ΣW i /ΣW ei in eq.…”
Section: Methodsmentioning
confidence: 99%
“…The values derived from the data of Cartwright et al (1977) /Trajmar et al (1984) are in agreement with the present results within the rather large error limits while those of Brunger and Teubner (1990) are not. Gillan et al (1996) reported recently differential cross sections for excitation of the A 3 + u state from R-matrix calculations. The 90 • values obtained by them at 10 and 15 eV impact energies have been scaled to correspond to the ν = 6 and ν = 4, 5, 6 excitations by the Franck-Condon factors of 0.082 and 0.198, respectively, and are shown in figure 9(a) and (b).…”
Section: Nitrogenmentioning
confidence: 99%
“…(b) Same as (a) except for excitation of the combined vibrational levels ν = 4, 5, and 6. The theoretical results of Gillan et al (1996) are also indicated by open triangles.…”
Section: Nitrogenmentioning
confidence: 99%